Noninvasive In Vivo Quantification of Neutrophil Elastase Activity in Acute Experimental Mouse Lung Injury. (18th September 2011) - Kossodo, Sylvie; Zhang, Jun; Groves, Kevin; Cuneo, Garry J.; Handy, Emma; Morin, Jeff; Delaney, Jeannine; Yared, Wael; Rajopadhye, Milind; Peterson, Jeffrey D.
Abstract : We developed a neutrophil elastase-specific near-infrared fluorescence imaging agent, which, combined with fluorescence molecular tomographic imaging, allowed us to detect and quantify neutrophil elastase activity in vivo, in real time, and noninvasively in an acute model of lung injury (ALI). Significantly higher fluorescent signal was quantified in mice with LPS/fMLP-induced ALI as compared to healthy controls, correlating with increases in the number of bronchoalveolar lavage cells, neutrophils, and elastase activity. The agent was significantly activated ex vivo in lung sections from ALI but not from control mice, and this activation was ablated by the specific inhibitor sivelestat. Treatment with the specific inhibitor sivelestat significantly reduced lung signal in mice with ALI. These results underscore the unique ability of fluorescence molecular imaging to quantify specific molecular processes in vivo, crucial for understanding the mechanisms underlying disease progression and for assessing and monitoring novel pharmacological interventions.